1997
DOI: 10.1021/op970105v
|View full text |Cite
|
Sign up to set email alerts
|

Amino Diol Based Asymmetric Syntheses of a Fused Benzazepine as a Selective D1 Dopamine Receptor

Abstract: A six-step practical synthesis of (6aS,13bR)-11-chloro-6,6a,7,8,9,13b-hexahydro-7-methyl-5H-benzo[d]naphtho-[2,1-b]azepin-12-ol, a selective D1 dopamine receptor, is developed starting from (1S,2S)-phenyl-2-amino-1,3-propanediol. An acid-promoted stereo-and regioselective cyclization of the benzazepine ring was established. Three double reactions in which two functional groups are transformed in a single step were developed. These include the double hydrolysis, the double reduction, and the cyclization and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The aminolactones are valued enough to access several synthetic targets. [8][9][10] Herein we report the catalytic and enantioselective aminolactonization of internal b,gand g,d-alkenoic acid esters that provides g and d-lactones, respectively, containing internal amino functionality with high diastereo-(dr 4 99 : 1) and enantio-selectivity (ee upto 94%) and also synthesis of aminolactones having an all-carbon quaternary stereo-centre with excellent diastereo-(dr 4 99 : 1) and enantioselectivity (ee upto 98%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The aminolactones are valued enough to access several synthetic targets. [8][9][10] Herein we report the catalytic and enantioselective aminolactonization of internal b,gand g,d-alkenoic acid esters that provides g and d-lactones, respectively, containing internal amino functionality with high diastereo-(dr 4 99 : 1) and enantio-selectivity (ee upto 94%) and also synthesis of aminolactones having an all-carbon quaternary stereo-centre with excellent diastereo-(dr 4 99 : 1) and enantioselectivity (ee upto 98%).…”
mentioning
confidence: 99%
“…The aminolactones are important structural motifs that are present in, or are precursors to, many biologically important compounds. 8,9 For example, aminolactones 3 can be easily transformed into b-benzyl-b-amino acids (Scheme 5), which are the key precursors to many compounds. 9 As an application, aminolactone 3g was converted to b-amino acid by reductive lactone opening.…”
mentioning
confidence: 99%
“…Apparently, several derivatives of A X X X X X X Scheme 2 Tautomerization of three series of benzocycloheptatrienes (nB X ) to their corresponding tricyclic benzonorcaradienes (nTX) for n = 1-3; and X = CH 2 , NH, and O; B = bicyclic; T = tricyclic azabenzocycloheptatrienes are considered as pharmacologically important molecules [16]. For example derivatives of 7H-7-azabenzocycloheptatriene serve as selective D 1 dopamine receptors and are useful in the treatment of psychose, depression, pain, and D 1 -dependent neurological disorders [17][18][19][20]. Similarly, derivatives of oxabenzocycloheptatrienes occur in natural products [21,22] and are used as natural herbicides [23].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, derivatives of oxabenzocycloheptatrienes occur in natural products [21,22] and are used as natural herbicides [23]. Hence, studying tautomerization and inversions of these biologically and pharmacologically interesting compounds provides an opportunity to disclose new aspects of their structural behavior [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…11 (F) It is shown that STAB-H effectively reduced amide 14 to 15 in the total synthesis of a selective D1 antagonist useful in the treatment of psychoses, depression, and D1-dependent neurological disorders. 12 (G) Cleavage of oxazolidines 16 can easily be carried out with STAB-H 13 to provide 17 and this tactic was featured in the first enantiospecific synthesis of salinosporamide A. 14…”
mentioning
confidence: 99%